Loss Aversion in Taste-Based Employee Discrimination: Evidence from a Choice Experiment - Louis Lippens; Stijn Baert; Eva Derous (Institute of Labor Economics (IZA), 2021)
Using a choice experiment, we test whether taste-based employee discrimination against ethnic minorities is susceptible to loss aversion. In line with empirical evidence from previous research, our results indicate that introducing a hypothetical wage penalty for discriminatory choice behaviour lowers discrimination and that higher penalties have a greater effect. Most notably, we find that the propensity to discriminate is significantly lower when this penalty is loss-framed rather than gain-framed. From a policy perspective, it could therefore be more effective to financially penalise taste-based discriminators than to incentivise them not to discriminate.
Keywords: J70; J24; J60; C92; 330; taste-based discrimination; employee discrimination; loss aversion; ethnicity